Reflection as teachers: Our critical developments - Cole, Chelsea; Hinchcliff, Elizabeth; Carling, Rylee (Frontiers in Education, 2022)
This study utilized Self-Study of Practice methodology (Pinnegar & Hamilton, 2009) to examine stories of our teacher development to explore the role of reflection in helping us grapple with challenging experiences in our teaching. Through emergent coding and collaborative analysis, we examine how reflection critically impacts the trajectory of practicing teachers. Our stories and subsequent discussion reveal recurring themes that suggest practices, attitudes, and skills reflective teachers implement to improve their understanding of the teacher-self and influence positive student outcomes.